2021
DOI: 10.3390/su132313138
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the Relationship between Place Attachment and Behavioral Intentions between 2010 and 2021: A Systematic Literature Review

Abstract: Place attachment is a key concept in understanding affective person–place relationships, and it provides an appropriate approach for the study of human behavior. This systematic literature review based on the PRISMA guidelines focuses on the relationships between place attachment and behavioral intentions. Due to the high number of studies that used place attachment as an independent or mediating variable, we categorized the studies into different research areas, which include business and management, risk and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 89 publications
0
21
0
Order By: Relevance
“…Place attachment is divided into four dimensions, namely, place identity, place dependence, place influence, and place social connection, so as to better explore its influence on TERB [ 23 ]. Previous research on place attachment has found that TERB in tourism contexts is significantly and positively influenced by place attachment, verifying that a deeper sense of place attachment will promote the implementation of TERB [ 24 ]. Destination attractiveness reflects the perception of visitors to the destination; it depends on whether the destination meets the needs of tourists and how tourist perceptions will influence the formation of place attachment [ 9 ].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Place attachment is divided into four dimensions, namely, place identity, place dependence, place influence, and place social connection, so as to better explore its influence on TERB [ 23 ]. Previous research on place attachment has found that TERB in tourism contexts is significantly and positively influenced by place attachment, verifying that a deeper sense of place attachment will promote the implementation of TERB [ 24 ]. Destination attractiveness reflects the perception of visitors to the destination; it depends on whether the destination meets the needs of tourists and how tourist perceptions will influence the formation of place attachment [ 9 ].…”
Section: Introductionmentioning
confidence: 80%
“…Moreover, different approaches have been adopted to measure destination attractiveness, including multi-attribute and single-item measures. Tourism destinations have various attributes that are different from tourist activities, such as transportation conditions, history and culture, and accommodation facilities, which are the attributes that make destinations attractive to tourists, drawing them away from their permanent residences [ 24 , 25 , 26 ]. Some scholars have suggested that tourism destination attractiveness is highly correlated with the level of tourism attraction and the quantity and quality of tourism facilities and service [ 23 ].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Place attachment research suggests that, in mobile lives with multiple place attachments, the time that is spent at the different places that are important to us shape our attachments to those particular places [27]. Different places are important for diverse social, cultural, and emotional reasons, as well as for practical purposes [18]. Seen in this light, the hypothesis that particular uses of, and particular attachments to, place levels can inform the stakeholder perceptions of RETs seems plausible.…”
Section: Finding Overview and Discussionmentioning
confidence: 99%
“…Place attachment has become an increasingly popular concept for understanding local responses to large-scale RETs (e.g., [18]). Van Veelen and Haggett [19] show that the place bond was an important motivator for the development of renewable energy projects, but that different degrees of place attachment also formed a key source of disagreement.…”
Section: People-place Relationsmentioning
confidence: 99%
“…Place attachment is thought to be the main way to capture affective person-place relationships (Dang & Weiss, 2021). It is important for researchers to follow the evolution of this psychological concept and get new insight into its effects with and on behaviors.…”
Section: Emotion (Affect)mentioning
confidence: 99%